Analysis of the Influence of Leadership Style, Job Promotion, And Work Motivation on Employee Job Satisfaction at Perumda Bank Perekonomian Rakyat - Nabila, Nanda Salsa; Ramdaniyah, Nur Laely; Maryam, Siti (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This investigation aimed to ascertain how leadership style, position promotion, and job motivation affected Perumda Bank Perekonomian Rakyat (BPR) employees’ job satisfaction. Design/methodology/approach: This study’s methodology is quantitative and makes use of primary data collected from 132 employees. Research instrument testing, multiple regression analysis, traditional assumption testing, and hypothesis testing are examples of data analysis techniques. To use “Statistical Product and Service Solution (SPSS) version 25” as a tool for data processing and computation when conducting research. Findings: The findings demonstrate that at Perumda Bank Perekonomian Rakyat (BPR), work motivation, leadership style, and position promotion all have a simultaneous and considerable influence on employee job satisfaction. Research limitations/implications: While there are several other elements that might also impact other employees’ job happiness, the three independent variables examined in this study are leadership style, promotion, and work motivation. Additionally, a questionnaire is used to collect data for this study, and the information gathered explains how Perumda Bank Perekonomian Rakyat (BPR) employees feel about their job satisfaction with the organization. Researchers have no control over the responses provided by respondents to each questionnaire. Practical implications: Lack of communication between leaders and employees and lack of space for employees to convey their input and aspirations. This implies that the lowest score on the employee job satisfaction variable needs to be improved by improving the compensation and benefits system so that employees feel valued and get proper welfare, establishing a welcoming and encouraging workplace to boost motivation and comfort among employees, providing career development programs and training to provide opportunities for employees to improve skills and career paths, implementing an objective and transparent performance appraisal system so that employees feel treated fairly in terms of promotions and awards and improving the balance between work and personal life with flexible work policies and proportional workloads. Originality/value: 87%. With the exception of a few brief quotes that are supplied as references, the researcher indicates that this study is unique and the first to be implemented at Perumda Bank Perekonomian Rakyat (BPR). Paper type: Research report